(untitled) (Global Journals of Research in Engineering, 2022)
In this paper a new idea is proposed to convert an omnidirectional monopole antenna into a directive antenna. The idea consists in loading the antenna by a block of dielectric material that redirects the wave radiation in its direction. Different design cases have been numerically studied, simulated and optimized by CST Microwave Studio. In each case the same idea has been confirmed.